Kajian Pencegahan Penularan HIV dari Ibu ke Anak pada Antenatal Care Oleh Bidan Praktik Mandiri di Yogyakarta - Inka Kartika Ningsih (Indonesian Journal of Health Administration (Jurnal Administrasi Kesehatan Indonesia), 2018)
In 2013, DIY AIDS prevalence was 23.75 %. ODHA reached 72.6% based on age class 25-49 years old. PMTCT programs were done to prevent HIV infection from mother to children. This research was a qualitative-descriptive research which has implemented the grounded theory. This research was conducted in Independent Midwifery Clinic Yogyakarta from March to June 2014. The respondents were midwives of Independent Midwifery Clinic, pregnant patients of the Independent Midwifery Clinic, midwife coordinators of primary public health care center, and family health care in Health Care Department of Yogyakarta. The first respondents were chosen with snowball sampling. Research instrument was manual interview, and the data were collected with in-depth interview. Data analysis was done with content analysis and data validation by using triangle source. The findings showed that PMTCT in ANC doesn’t work effectively in Independent Midwifery Clinic Yogyakarta. Midwives play role as the guides for pregnant mothers to get ANC in primary public health center. Counseling and bargaining about HIV diagnostic can decrease the stigma and discrimination in society. The implementation of HIV infection prevention (PPIA) may invite the cadres and all of public sectors to collaborate.  Keywords: antenatal care, HIV, PPIA